Health Services, Maternal Intrinsic and Socio-Cultural Factors and Perinatal Mortality (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
This study question was how significant the determination of health services, maternal intrinsic risk factors and socio-cultural factors on perinatal mortality. Its objective was to construct a model of perinatal mortality pattern by case-control design. The case population was all mothers with perinatal mortality. The sample-size was 35 by simple random sampling with case-control ratio of 1:1 (35:35). The data analysis applied Bivariate using Chi Square Test and Multivariate using Logistic Regression Test. The Bivariate Analysis Results found the risk-variables on Perinatal Mortality were Birth Attendant (OR=2.1; 1.63-2.7; 95%CI), Health Financing (OR=7.1; 1.82-27.8; 95% CI), Maternal Disease History (OR=8; 2.05-31.16; 95%CI), Perinatal History (OR=6.47; 2.26-18.55; 95%CI) and Custom (OR=2.17; 1.67-2.82; 95%CI). Multivariat Analysis found three consistent risk variables on Perinatal Mortality i.e.: Health Financing (p=0.016; OR=6.8; 95% CI), Maternal Disease History (p=0.006; OR=8.41; 95%CI) and Perinatal History (p=0.021; OR=4.3; 95%CI). It concluded that the most significant determinant on Perinatal Mortality was Maternal Disease History.